Práticas comunicacionais de combate ao trabalho escravo do ministério público do trabalho no Maranhão - NICOLAU, Wanderson Ney Lima Rodrigues (2021)
Study about communicational practices of slavery combat from the Public Ministry of Labor in Maranhão {MPT-MA). Performs analysis on the categories of communication and slavery, based on the approaches of Kunsch (2003; 2016), Henriques (2012), Castells (2003; 2007; 2009; 2011; 2013), Lévy (1993; 1998; 2000), Moura (2009; 2016; 2020), Esterci (1994), among others. It typifies the research as a bibliographic and documentary study, of a prospective, descriptive and analytical character, with a quali-quanti approach, presenting a brief report on the historiography of slavery in Brazil and carrying out data mining on the performance of the MPT-MA in combating slavery. Itaims to map the main communicational practices of slavery combat by MPT-MA, in addition to mapping the contributions of different audiences to the communication flows of the MPT-MA and analyzing the work routine of the MPT-MA's Social Communication Department. It presents the launch of a product called the Communication Practices Protocol for Strengthening the Fight against Slave Labor by the Public Ministry of Labor in Maranhão (MPT-MA).